Complete Maxillo-Mandibular Syngnathia in a Newborn with Multiple Congenital Malformations - M. Broome; Y. Vial; S. Jacquemont; C. Sergi; D. Kamnasaran; E. Giannoni (Pediatrics and Neonatology)
Syngnathia is an extremely rare condition involving congenital fusion of the maxilla with the mandible. Clinical presentations vary from simple mucosal bands (synechiae) to complete bony fusion (synostosis). Most cases are unilateral incomplete fusions. We report the case of a severely growth-retarded newborn infant with complete synostosis of the mandible with the maxilla and the zygoma associated with cleft palate, choanal atresia, deafness, delayed cerebral white matter development, and genital and limb malformations. Extensive genetic analysis did not reveal any mutations. This association of multiple congenital malformations may represent an entity distinct from previously described syndromes associated with syngnathia.